2017
DOI: 10.1108/ijebr-02-2017-0070
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to rural women entrepreneurs in Oman

Abstract: Purpose: Analyses barriers confronted by women entrepreneurs living and running businesses in rural Oman. The study identifies numerous problems including: accessing funding for new ventures and innovative activities, a lack of skills based training and limited family support.Design/methodology/approach: Draws on 57 responses to a semi-structured questionnaire, and face to face qualitative interviews with five women entrepreneurs. Quantitative responses are evaluated and ranked in terms of their mean score, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(116 citation statements)
references
References 45 publications
7
108
0
1
Order By: Relevance
“…The research, supported by Lindvert et al (2015), concluded that government support is crucial for entrepreneurship; yet women perceive that the government will not provide adequate support and thus avoid asking for assistance. Ghouse et al (2017) found that female entrepreneurs identified that support and incentive from the government are difficult to find, supporting the findings of the study. Di Gregorio (2013) found that value creation emerged from the opportunities and resources available to develop new business and increase revenue.…”
Section: Inadequate Support From the Governmentsupporting
confidence: 84%
See 3 more Smart Citations
“…The research, supported by Lindvert et al (2015), concluded that government support is crucial for entrepreneurship; yet women perceive that the government will not provide adequate support and thus avoid asking for assistance. Ghouse et al (2017) found that female entrepreneurs identified that support and incentive from the government are difficult to find, supporting the findings of the study. Di Gregorio (2013) found that value creation emerged from the opportunities and resources available to develop new business and increase revenue.…”
Section: Inadequate Support From the Governmentsupporting
confidence: 84%
“…In this research, 89% of participants operated businesses in the service sector perceived suitable for women. The findings remain consistent with Ghouse et al (2017), who confirmed that family ambivalence, gender bias, and social norms act as obstacles to female entrepreneurial ability.…”
Section: Society's Perception Of Suitable Work For Womensupporting
confidence: 83%
See 2 more Smart Citations
“…Women are overloaded with the double burden of managing their businesses and of caring for their families (Agarwal and Lenka 2015;Stoner, Hartman and Arora 1990;Rehman and Roomi 2012). As such, women continue to have inadequate entrepreneurial knowledge of their surroundings, have limited experience in creating networks and miss the opportunity to participate in activities conducted by the associations (Ghouse et al 2017;Mazlina and Punitha 2016;Ilhaamie et al 2014).…”
Section: Literature Review Women Entrepreneurship In Malaysiamentioning
confidence: 99%